Evaluation of Rehabilitation Strategies and Management Schemes for the Improvement of Mangrove Management Programs in Lingayen Gulf - Salmo III, Severino; Torio, Dante; Esteban, Janalezza Morvenna (Science Diliman: A Journal of Pure and Applied Sciences; Vol 19 No 1 (2007), 2007)
We evaluated the mangrove rehabilitation strategies and management schemes in five municipalities in Lingayen Gulf (Bolinao, Anda, Bani, Alaminos and San Fernando). Mangrove planting appears to be the first and only option used in the area, ignoring other recommended management strategies, e.g. conservation, landscaping, and sustainable production. All planting sites were located in coastal fringes and are mostly monospeficic stands of the species Rhizophora mucronata. The planted mangroves were constrained by low seedling survival and stunted growth as probably caused by poor species-substrate matching, mono-species planting and pest infestations. Three management schemes were noted: community-managed (Bolinao and Anda), local government unit (LGU)-managed (Alaminos and San Fernando), and co-managed between the LGU and the community (Bani). The community-managed mangrove areas have the benefits of voluntary efforts from community-based organizations in conducting daily management activities but were constrained with budgetary and logistical concerns. In contrast, both LGU-managed and co-managed areas received institutional and logistical supports from their respective municipal governments, but lacking community participation made mangrove management difficult. Almost two decades of mangrove management indeed helped improved the mangrove forest condition, at least in terms of forest structure. These projects demonstrated some level of success but also encountered several setbacks. Several lessons can be derived from these areas that can help improve the mangrove rehabilitation and management approaches in Lingayen Gulf. Among the recommendations are: (1) provide ordinance enacting the remaining natural secondary growth mangroves as marine protected areas, (2) promote planting in former mangrove areas by reverting abandoned, idled and unproductive aquaculture ponds to mangroves; (3) improve management schemes by formulating resource management plan, institutionalizing annual budget allocation, enhancing community participation, and enhancing tenurial instrument; and (4) incorporate periodic project evaluation.